Acute exposure to diesel affects inflammation and vascular function. (29th January 2020) - Tousoulis, Dimitris; Fountoulakis, Petros; Oikonomou, Evangelos; Antoniades, Charalambos; Siasos, Gerasimos; Tsalamandris, Sotirios; Georgiopoulos, Georgios; Pallantza, Zoi; Pavlou, Efthimia; Milliou, Antigoni; Assimakopoulos, Margarita N; Barmparesos, Nikolaos; et al.
Abstract: Background: Diesel exhaust fumes represent one of the most common toxic pollutants. The prolonged effects of acute exposure to this pollutant on inflammatory status and vascular properties are unknown. Methods: During a 2-h session, 40 healthy subjects were exposed to diesel exhaust fumes and/or filtered air. Endothelial function was assessed with flow mediated dilation, arterial stiffness with pulse wave velocity and reflected waves with augmentation index. C-reactive protein, fibrinogen, protein C levels and protein S activity were also measured. Standard deviation of normal to normal R–R intervals (SDNN) was used to assess heart rate variability. Measurements were assessed before exposure and 2 and 24 h after diesel exposure. Results: Compared with filtered air, exposure to diesel exhaust fumes decreased flow mediated dilation and increased pulse wave velocity and augmentation index up to 24 h after the exposure ( p  < 0.001 for all). Similarly, compared with filtered air, diesel exhaust exposure impaired SDNN during the 24-h study period ( p  = 0.007). C-reactive protein and fibrinogen levels were significantly increased after diesel exhaust exposure while protein C levels and protein S activity decreased ( p  < 0.01 for all). Exposure to diesel exhaust fumes resulted in higher C-reactive protein concentration in smokers compared with non-smokers ( p  < 0.001). Conclusion: Short-term exposure to diesel exhaust fumes has a prolonged adverse impact on endothelial function and vascular wall properties, along with impaired heart rate variability, abnormal fibrinolytic activity and increased markers of inflammation. These findings give insights into the mechanisms underlining the increased cardiovascular risk of subjects regularly exposed to diesel exhaust fumes.